Bringing Reflective Functioning to the Community: Aspects of psychotherapy process in the Group Attachment Based Intervention. Issue 1 (31st December 2022) - Steele, M.; Steele, H.; Murphy, A.
ABSTRACT: This special section dedicated to papers concerned with change processes in psychodynamic child and adolescent psychotherapy poses a set of interesting questions. What makes an intervention psychodynamic? How do we measure psychotherapy process? How can we bring psychodynamically-oriented treatment to a wider community, especially those that would not otherwise have access? These questions highlight the rich dialogue that can take place when we draw on psychoanalytic constructs and techniques to inform clinically relevant research, and then extrapolate these, to bring treatment to where they are desperately needed.